2009
DOI: 10.1080/09637480802167425
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to healthy eating among a representative sampling of Croatian adults: A comparison with Mediterranean countries

Abstract: The objectives of this study were to examine the understanding of healthy eating, to assess the perceived need to change eating habits, to identify information sources about healthy eating among Croatian adults and to compare it with other Mediterranean countries. The sample included 1,006 randomly selected Croatian subjects over 15 years of age. The questions were adapted from the Pan-European Survey (1995-1996). A total of 50% of the participants described healthy eating as 'fresh and natural foods', more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Pirouznia (2001) found that NK among adolescents had an impact on eating behaviour. Several other studies (Shah et al, 2010;Ranilović et al, 2009;Satia et al, 2010) also demonstrated that a relationship exists between NK and food choices. Questions evaluating respondents' level of NK, both general and dairy product specific, were included in the survey instrument and are included in the analysis of dairy anti-consumption to see whether they play a role.…”
Section: Introductionmentioning
confidence: 85%
“…Pirouznia (2001) found that NK among adolescents had an impact on eating behaviour. Several other studies (Shah et al, 2010;Ranilović et al, 2009;Satia et al, 2010) also demonstrated that a relationship exists between NK and food choices. Questions evaluating respondents' level of NK, both general and dairy product specific, were included in the survey instrument and are included in the analysis of dairy anti-consumption to see whether they play a role.…”
Section: Introductionmentioning
confidence: 85%
“…The dietary habits of the patients were not analyzed in our study, although we hypothesized that a large proportion of patients follow the Mediterranean diet. Ranilovic et al (48) reported that Croats have the most similar dietary habits to the Italian population. The Mediterranean diet is rich in unsaturated omega-3 fatty acids, which may have affected our results.…”
Section: Alelle (%) Genotype (%) ------------------------------------mentioning
confidence: 99%
“…The research in the field of food science have showed the existence of different volitional factors in the case of gender, which directly or indirectly are related to eating behaviour [9,17,18].…”
Section: Discussionmentioning
confidence: 99%